Science examinations in environmental knowledge classes: experiences of a tutoring program from the point of view of the tutors (Training and Practice : Journal of Educational Sciences, 2023)
The development program we examined took place through the application of cross-aged peer tutoring. Sixth-grade tutors and fourth-grade students (tutees) participated in the research. The main aim of the program is to encourage students to conduct simple experiments in line with the science subject curriculum. The experiments are guided by older students. We were interested in what impressions the tutors had of the session series. We examined the experiences of tutor students (N = 12) with a program evaluation questionnaire containing open and closed questions. The tutor students applied for the program because they found it interesting. The aim of the program, according to the tutors, was to try out the teacher’s role. They liked the guiding experiments and teaching the fourth graders the most, and the biggest challenge was disciplining the students and arousing their interest.
Keywords: peer learning; tutor students; elementary school; science education